2000
DOI: 10.1084/jem.192.9.1327
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Prostaglandin F2α Synthase in Trypanosoma brucei

Abstract: Members of the genus Trypanosoma cause African trypanosomiasis in humans and animals in Africa. Infection of mammals by African trypanosomes is characterized by an upregulation of prostaglandin (PG) production in the plasma and cerebrospinal fluid. These metabolites of arachidonic acid (AA) may, in part, be responsible for symptoms such as fever, headache, immunosuppression, deep muscle hyperaesthesia, miscarriage, ovarian dysfunction, sleepiness, and other symptoms observed in patients with chronic African tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
93
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 58 publications
(59 reference statements)
4
93
1
1
Order By: Relevance
“…The rationale used for substrates. This finding is consistent with our site-directed mutagenesis data and explains our previous results showing that the reduction of PGH 2 by TbPGFS was not inhibited by 9,10-PQ when both substrates were incubated simultaneously in excess (31). A profile of the k cat versus pH for the tetrad mutants revealed that mutants Y52F, K77L, H110A, and H110F eliminated the titratable group for 9,10-PQ reduction.…”
supporting
confidence: 82%
See 4 more Smart Citations
“…The rationale used for substrates. This finding is consistent with our site-directed mutagenesis data and explains our previous results showing that the reduction of PGH 2 by TbPGFS was not inhibited by 9,10-PQ when both substrates were incubated simultaneously in excess (31). A profile of the k cat versus pH for the tetrad mutants revealed that mutants Y52F, K77L, H110A, and H110F eliminated the titratable group for 9,10-PQ reduction.…”
supporting
confidence: 82%
“…Enzyme Assay and Kinetic Measurements-PGH 2 reductase activity was measured by incubating at 37°C for 2 min a reaction mixture containing an appropriate enzyme aliquot, 5 M [1-14 C]PGH 2 (final concentration), 100 l of 100 mM sodium phosphate (pH 7.0), and 500 M NADPH (31). After the reaction had been terminated by the addition of 250 l of stop solution (30:4:1 (v/v/v) diethyl ether/methanol/2 M citric acid), aliquots were analyzed by thin-layer chromatography as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations